Integrated comparison of the miRNAome and mRNAome in muscles of dermatomyositis and polymyositis reveals common and specific miRNA–mRNAs. (7th December 2018) - Gao, Siming; Zhang, Huali; Zuo, Xiaoxia; Xiao, Yizhi; Liu, Di; Zhu, Honglin; Luo, Hui
Aim: Dermatomyositis (DM) and polymyositis (PM) are refractory systemic autoimmune diseases with unknown pathogenesis. miRNAs is an important epigenetic mechanism to regulate gene expression.Methods: We performed whole miRNAs analysis, transcription analysis and the association between miRNAome and mRNAome.Results: For transcription and miRNAs analysis, there were common and specific mRNAs and miRNAs in the muscles of DM and PM. Among them, the expression levels of miR-196a-5p and CPM were negatively correlated in PM, miR-193b-3p and NECAP2 were negatively correlated in DM and PM. Protein carboxypeptidase M (CPM) plays roles in the degradation of extracellular proteins and in the migration and invasion of cancer cells, and protein NECAP2 plays roles in adaptor protein AP-1-mediated fast recycling from early endosomes. The functions of them in the pathogenesis of DM/PM need further studies.Conclusion: Our study identified and confirmed differentially miRNAs and mRNAs in DM and PM. Our observations have laid the groundwork for further diagnostic and mechanistic studies of DM and PM.